2006
DOI: 10.5016/1806-8774.2003v5p39
|View full text |Cite
|
Sign up to set email alerts
|

<b>The Importance of Animal Well-being for Reproduction in Captive <b/>

Abstract: International zoos consider enrichment to be very important, with many reports in the literature confirming the efficacy of interactive techniques used with the exclusive objective of providing a better quality of life, with the consequent well-being and reproductive success of animals held in captivity. It is difficult to measure effectively well-being, but indirect measurements are considered to be reliable, such as physical health, physiological measurements of stress, and presentation of the typical behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Some studies report that visitors can be a stress factor for animals in captivity (Nimon and Dalziel 1992;Maia et al 2012), especially when environments lack adequate stimuli. According to Pizzutto (2006), when an environment presents adequate and satisfactory stimuli for a species in captivity, stress stimuli become less influential and cause less damage to the animals' natural behaviors. Although the visitor's interference in the animals' behavior has not been evaluated, our results showed that the enrichment items were able to attract Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that visitors can be a stress factor for animals in captivity (Nimon and Dalziel 1992;Maia et al 2012), especially when environments lack adequate stimuli. According to Pizzutto (2006), when an environment presents adequate and satisfactory stimuli for a species in captivity, stress stimuli become less influential and cause less damage to the animals' natural behaviors. Although the visitor's interference in the animals' behavior has not been evaluated, our results showed that the enrichment items were able to attract Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os estudos, 90% se demonstraram efetivos na redução de comportamentos anormais durante a aplicação do enriquecimento, quando comparados aos dados da linha de base (anterior a aplicação do enriquecimento). Além da redução de comportamentos anormais, as técnicas de enriquecimento dão assistência para os processos reprodutivos (Díez-Léon et al, 2013;Carlstead & Shepherdson, 1994;Pizzutto, 2003), para reintrodução de animais selvagens (Reading et al, 2013), e aumento de comportamentos ativos e exploratórios (Machado & Genaro, 2010), assim como aumento de comportamentos espécie-específicos (VandeWeerd et al, 2006), redução na agressão (Mellottiet al, 2011;VandeWeerd et al, 2006;Mork et al, 1999), dentre outros benefícios para o bem-estar dos animais.…”
unclassified
“…Among the studies, 90% were effective in decreasing abnormal behaviours during the application period, when compared to data collected during the baseline period (prior to enrichment introduction). Besides a reduction in abnormal behaviours, enrichment techniques can assist in reproductive success (DÍEZ-LÉON, et al, 2013;SHEPHERDSON, 1994;PIZZUTTO, 2003), the reintroduction process of wild animals (READING; MILLER; SHEPHERDSON, 2013), activity and exploratory behaviours increase (MACHADO; GENARO, 2010), as well as species-specific behaviours (VAN DE WEERD et al, 2006), a reduction in aggression (MELLOTTI, et al, 2011;VAN DE WEERD et al, 2006;MORK;BJERKENG;RYE, 1999), and other benefits to animals' welfare.…”
Section: Concept and Historymentioning
confidence: 99%